Energy harvesting via fluidic agitation of a magnet within an oscillating heat pipe. (25th January 2018) - Monroe, J. Gabriel; Ibrahim, Omar T.; Thompson, Scott M.; Shamsaei, Nima
Highlights: Oscillating heat pipes (OHPs) can be used for thermal energy conversion. Fluid motion within an OHP can agitate a suspended magnet for induction. Thermal performance of OHP harvester increases at cost of power generation. Suspending larger magnets within OHP tube can increase power generation. OHP harvester is a portable means for electric power generation. Abstract: An 'oscillating magnet' energy harvesting module was developed and integrated into a 4-turn, tubular oscillating heat pipe (OHP) filled with water. The harvesting module consisted of a 1000-turn solenoid wrapped around a polycarbonate tube and two transverse posts, which were placed through the tube above and below the solenoid. Electromagnetic induction was accomplished via the thermally-driven, fluidic agitation of a suspended neodymium magnet placed between the transverse posts. The thermal performance and energy harvesting ability of this 'oscillating-magnet OHP' (OMHP) was experimentally investigated over a range of heat inputs with either 1.59 mm or 3.17 mm diameter neodymium magnets. Results demonstrate that the OMHP heat transfer performance decreased as the magnet diameter approached that of the OHP tube due to increased local pressure drops across the magnet, which disrupted advection between the evaporator and condenser. At 400 W of heat input, the OMHP equipped with a smaller oscillating magnet ( i.e. 1.59 mm diameter) produced a maximum peak electrical power of 21.9 µW and provided an effective thermal conductivity of ∼7000 W/m K. In contrast, the OMHP equipped with a larger oscillating magnet ( i.e. 3.17 mm diameter) produced a maximum peak electrical power of 428 µW and an effective thermal conductivity of ∼2600 W/m K at 200 W of heat input. Since the confined magnet motion is coupled with the heat transfer and internal fluid motion of the OHP, the design of the OMHP is driven by the importance of energy harvesting relative to thermal performance. This technology is unique in that it can be used for thermal management and in situ electric power production.